Kontribusi Taman Kanak-kanak salam Mengembangkan Aspek Perkembangan Anak Usia Dini di Desa Rantau Sentosa Kecamatan Busang Kabupaten Kutai Timur - Aslindah, Andi; Suriyani, Lilis (PT Literasi Nusantara Publisher, 2024)
This study aims to determine the contribution of Tunas Harapan kindergarten buds of hope in developing aspect of early childhood development in Rantau Sentosa Village, Busang District, East Kutai Region. This research used a qualitative approach, with data collection obtained through observation, interviews and documentation. The subjects in this study were the parents of Tunas Harapan Kindergarten students. From the results of the data analysis, it is concluded that Tunas Harapan Kindergarten has contributed to developing aspect of development in children from an early age; religious and moral development of children, physical motoric development of children, cognitive development and aspects of social emotional development in children. However, there are also aspects of development that have not developed optimally, namely, aspects of language development and art development. This is due of the obstacles encountered, namely; 1) obstacle is the majority of people in the neighborhood speak regional languages, so that making it difficult for children to speak Indonesian; 2) obstacle is that the teacher of Tunas Harapan Kindergarten have not been able to attract children attention to learning art, where the teachers do not have more knowledge of art. The teacher strategy in overcoming these obstacles, namely; teacher continue to learn from books about art to teach children, and teacher continue to try to get the children to say one sentence in Indonesian every day.